Effect of macromolecules on varying collagen concentration - Ang, Michelle Hwei Xin (2016)
The dermal layer of the skin is divided into a papillary region and a reticular region with varying collagen fiber thicknesses and different fiber orientations. Thus to fabricate an ideal scaffold to replace the dermis, the scaffold ought to have the main features of the dermis. To be able to fabricate such a scaffold, it requires modification of the scaffold architecture. In this project, the biomaterial used for scaffold fabrication is collagen type I as it is one of the most commonly used materials and offers many advantages. To tune the architecture of the collagen, there are various ways and macromolecular crowding (MMC), which results macromolecules occupying space and leading to fractional volume occupancy (FVO), is utilized in this project. The effect of macromolecular crowding on the collagen architecture, namely the collagen fiber diameter and porosity, will be studied. The selected type of macromolecules is Polyvinylpyrrolidone (PVP)360 kDa and FVOs of 0%, v/v, 18% v/v, 36% v/v and 54% v/v are shortlisted to be used induce the MMC effect. Collagen scaffolds of different concentrations, 1.5 mg/ml and 3 mg/ml, will be fabricated. Characterization of the scaffolds will be completed through using the field emission scanning electron microscope to capture images and ImageJ to process the images. For both of the concentrations, the collagen fiber diameter was observed to increase along an increase in the FVOs of PVP 360kDa. As for porosity, it was found to decrease along an increase in the FVOs.